Exploring linguistic complexity of English First Additional Language Grade 12 and Grade 11 exam texts (Journal of the Digital Humanities Association of Southern Africa, 2023)
This article investigates consistency and levelness of texts administered for English First Additional Language exams in grade 11 and grade 12. The analysis is based on a data set comprising 80 texts extracted from 20 question papers from the year 2011 to the year 2020. The exam texts are separated into reading comprehension, summary writing and language and editing texts. A total of 18 indices were analysed. Aspects covering lexical diversity, syntactical complexity, text readability, the use of connectives and surface level complexity were analysed. The findings indicate that grade 12 exam texts are consistently more linguistically complex than grade 11 exam texts. Grade 12 exam texts are also found to be more lexically diverse and syntactically complex than grade 11 exam texts. Furthermore, grade 12 exam texts are harder to read than grade 11 exam texts. For both grades, summary writing texts are easier to read.
Keywords: Linguistic complexity; English first additional language; Lexical diversity; Text readability